Atypical manifestation of parathyroid carcinoma with late-onset distant metastases. (28th October 2017) - Tsoli, Marina; Angelousi, Anna; Rontogianni, Dimitra; Stratakis, Constantine; Kaltsas, Gregory
Summary: Parathyroid carcinoma is an extremely rare endocrine malignancy that accounts for less than 1% of cases of primary hyperparathyroidism. We report a 44-year-old woman who presented with fatigue and diffuse bone pain. Laboratory findings revealed highly elevated serum calcium and parathyroid hormone (PTH) levels and a 4.5 × 3 × 2.5 cm cystic lesion in the lower pole of the right thyroid lobe that was shown histologically to be a parathyroid carcinoma. Ten years later, the patient developed brain and pulmonary metastases and recurrence of PTH-related hypercalcemia. Treatment of hypercalcemia along with localized radiotherapy and various chemotherapy regimens failed to induce a biochemical or radiological response. In conclusion, parathyroid carcinoma is a rare neoplasia that may develop metastases even after prolonged follow-up, for which there is no evidence-based treatment besides surgery. Different chemotherapeutic schemes did not prove to be of any benefit in our case highlighting the need for registering such patients to better understand tumor biology and develop specific treatment. Learning points: Metastases can develop many years after parathyroid cancer diagnosis. Surgery is the only curative treatment for parathyroid carcinoma. Chemotherapy and radiotherapy prove to be ineffective in parathyroid cancer treatment. Patient registering is required in order to delineate underlining pathology and offer specific treatment.